Abiraterone and Olaparib for Metastatic Castration-Resistant Prostate Cancer - Clarke, Noel W; Armstrong, Andrew J; Thiery-Vuillemin, Antoine; Oya, Mototsugu; Shore, Neal; Loredo, Eugenia; Procopio, Giuseppe; de Menezes, Juliana; Girotto, Gustavo; Arslan, Cagatay; Mehra, Niven; Parnis, Francis; et al. (NEJM evidence, 2022)
BACKGROUND: Preclinical studies and results of a phase 2 trial of abiraterone and olaparib suggest a combined antitumor effect when the poly(adenosine diphosphate[ADP]-ribose) polymerase inhibitor olaparib is combined with next-generation hormonal agent abiraterone to treat metastatic castration-resistant prostate cancer (mCRPC). METHODS: We conducted a double-blind, phase 3 trial of abiraterone and olaparib versus abiraterone and placebo in patients with mCRPC in the first-line setting. Patients were enrolled regardless of homologous recombination repair gene mutation (HRRm) status. HRRm status was determined following enrollment by tumor tissue and circulating tumor DNA tests. Patients were randomly assigned (1:1) to receive abiraterone (1000 mg once daily) plus prednisone or prednisolone with either olaparib (300 mg twice daily) or placebo. The primary end point was imaging-based progression-free survival (ibPFS) by investigator assessment. Overall survival was among the secondary end points. RESULTS: At this planned primary analysis at the first data cutoff, median ibPFS was significantly longer in the abiraterone and olaparib arm than in the abiraterone and placebo arm (24.8 vs. 16.6 months; hazard ratio, 0.66; 95% confidence interval [CI], 0.54 to 0.81; P<0.001) and was consistent with blinded independent central review (hazard ratio, 0.61; 95% CI, 0.49 to 0.74). At this data cutoff, overall survival data were immature (28.6% maturity; hazard ratio, 0.86; 95% CI, 0.66 to 1.12; P=0.29). The safety profile of olaparib and abiraterone was consistent with the known safety profiles of the individual drugs. The most common adverse events in the abiraterone and olaparib arm were anemia, fatigue/asthenia, and nausea. CONCLUSIONS: At primary analysis at this first data cutoff, abiraterone combined with olaparib significantly prolonged ibPFS compared with abiraterone and placebo as first-line treatment for patients with mCRPC enrolled irrespective of HRRm status. (Funded by AstraZeneca and Merck Sharp & Dohme, LLC, a subsidiary of Merck & Co., Inc., Rahway, NJ, USA; ClinicalTrials.gov number, NCT03732820.)
Keywords: Antineoplastic Combined Chemotherapy Protocols; Phthalazines; Prostatic Neoplasms, Castration-Resistant; nádory prostaty rezistentní na kastraci; Piperazines; protokoly protinádorové kombinované chemoterapie; ftalaziny; Humans; mužské pohlaví; Male; lidé; androsteny; Androstenes; piperaziny